The relationship between person environment (P-E) fit and employees’ job performance: the moderating role of work involvement in ministry of home affairs / Ayu Kamareenna Abdullah Thani - Abdullah Thani, Ayu Kamareenna (2019)
This study examined the relationship between person environment (P-E) fit,work involvement and employees' job performance in Ministry of Home Affairs. A total of 376 questionnaires were distributed and 371 questionnaires were collected, with a response rate of 98.67%. The SPSS version 23 was used for analysis. Person-environment fit consisted of person-job fit, person-organization fit, person-group fit and person-supervisor fit. Job Performance was measured in terms of task performance and organizational citizenship behavior (OCB). The first objective was to investigate the influence of dimensions of person-environment (P-E) fit on job performance among public servants. The study found that person-group fit and person-supervisor fit are significant in predicting task performance. For second dimension of dependent variable (i.e OCB), only person-supervisor fit is significant. The second objective was to investigate the moderating role of work involvement in influencing the link between dimensions of person- environment (P-E) fit and job performance among public servants. Work involvement has no moderating role in influencing person-environment fit dimensions and task performance. Besides, work involvement has moderation effect on the relationship between person-job fit, person-organization fit and person-supervisor fit and OCB. It can be concluded that, work involvement is a moderator for the link between person-job fit, person-organization fit and person-supervisor fit and OCB as the dependent variable. Meanwhile the other dimension of person-environment fit (i.e person-group fit) shows no moderation effect on the relationship with OCB. It can be concluded that, work involvement is not moderator for the link between person-group fit and OCB as dependent variable and the hypothesis is not supported. Finally, theoretical, practical and methodological contributions as well as directions for future research were discussed. This study has given some additional implications in terms of methodological aspects, particularly source of rating method and statistical analyses using SPSS. This study has adopted an approach of a self-performance rating to evaluate job performance among public servants. Based on the research results and discussions, the study sample could be extended to a larger population, i.e. the different ministries in all states Malaysia. This study also suggests future works to apply the supervisory-rating specifically in measuring the performance of the workers.